Vote Buying or Campaign Promises? Electoral Strategies When Party Credibility is Limited - Marek Hanusch; Philip Keefer; Razvan Vlaicu (Inter-American Development Bank (IDB), 2016)
What explains significant variation across countries in the use of vote buying instead of campaign promises to secure voter support? This paper explicitly models the tradeoff parties face between engaging in vote buying and making campaign promises, and explores the distributional consequences of this decision, in a setting where party credibility can vary. When parties are less credible they spend more on vote buying and target vote buying more heavily toward groups that do not believe campaign promises. When political credibility is sufficiently low, some voter groups are targeted only with vote buying and not with promises of post-electoral transfers. Stronger electoral competition reduces rent seeking but increases vote buying. Incumbents may have an advantage in undertaking vote buying; the paper finds that in a dynamic setting the prospect of a future incumbency advantage increases current vote buying.
hdl:11319/7775
Keywords: D72; H20; H50; O10; 330; Vote buying; Campaign promises; Credibility; Rent seeking